Socialization of the Introduction of the Halal Concept and the Legality of Womenpreneurs Products - Ifahda Pratama Hapsari; Vembri Aulia Rahmi; Hardian Iskandar (OJS Universitas Muhammadiyah Gresik, 2023)
This community service activity was inspired by small-scale micro-enterprises managed by the Kenanga cooperative which was founded in 2019 supported by PKK women and also by Lecturers who gave educational lectures on the introduction of the halal concept and how to obtain product legality. The purpose of this activity is to provide additional support for scientific solutions for the educational team related to the field of law and entrepreneurship. Train to use media and art materials through creative principles, and be environmentally friendly Produce works that are scientific and educational in nature and ready to be used in life, are knowledge and foundational for development based on local wisdom technology and renewable technology. of the product being developed goes on.